2023
DOI: 10.1002/pbc.30700
|View full text |Cite
|
Sign up to set email alerts
|

Financial burden and recommended multilevel solutions among caregivers of pediatric hematopoietic stem cell transplant recipients

Austin R. Waters,
Caitlin B. Biddell,
Mary Killela
et al.

Abstract: BackgroundThe healthcare costs of patients who receive hematopoietic stem cell transplantation (HSCT) are substantial. At the same time, the increasing use of pediatric HSCT leaves more caregivers of pediatric HSCT recipients at risk for financial burden—an understudied area of research.MethodsFinancial burden experienced by caregivers of recipients who received autologous or allogeneic transplants was assessed using an explanatory mixed‐methods design including a one‐time survey and semi‐structured interviews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Future OFN interventions may be a promising approach to addressing FT affecting dyads by helping manage finances, optimizing health insurance use, applying for financial assistance programs, and providing pre‐treatment cost estimates and access to transportation/food assistance 11–16 . Additional, potentially individually‐delivered interventions may be needed to address FT through educational programs (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Future OFN interventions may be a promising approach to addressing FT affecting dyads by helping manage finances, optimizing health insurance use, applying for financial assistance programs, and providing pre‐treatment cost estimates and access to transportation/food assistance 11–16 . Additional, potentially individually‐delivered interventions may be needed to address FT through educational programs (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Caregivers also report neglecting their own physical and mental health to cope with the financial burden related to their loved one's cancer treatment. 11 Despite this considerable caregiving burden, relatively few dyad-based studies have demonstrated the shared psychosocial experiences of hematologic patients and their caregivers, especially those undergoing BMTs. Even fewer assess the dyadic experiences of FT in this population.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations